A revision of some “Iberian” inscriptions from the Balearic Islands (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
This paper revisits two graffiti from the Roman city of Pollentia (Alcúdia, Majorca) and one of the legends of a group of locally issued coin-shaped lead tokens. The three inscriptions were previously regarded as Iberian, but in all probability they are Latin. The graffiti seem to be indications of ownership, one containing a name of Punic origin and the other a Latin name, whereas the reading of the legends is very doubtful. The study also discusses a lead tablet of unknown provenance bearing a text that has been regarded as Iberian. There can be no doubt that it is a modern forgery.
Keywords: Latin epigraphy; Iberian epigraphy; Anthroponymy; Numismatics; Lead tablets